Quercus acuta Thunb. Suppresses LPS-Induced Neuroinflammation in BV2 Microglial Cells via Regulating MAPK/NF-κB and Nrf2/HO-1 Pathway - Jae Kwang Kim; Hye Jin Yang; Younghoon Go (MDPI AG, 2022)
Microglial activation-mediated neuroinflammation is associated with the pathogenesis of neurodegenerative disorders. Therefore, the management of microglial cell activation and their inflammatory response is an important therapeutic approach for preventing neurodegenerative diseases. Quercus acuta Thunb. (QA) (Fagaceae) is a tree found in Korea, China, and Japan. The current study investigated the anti-neuroinflammatory effects of QA and its mechanism of action in lipopolysaccharide (LPS)-stimulated BV2 microglial cells. Pretreatment with a methanol extract of dried QA stems (QAE) inhibited the production of nitric oxide and proinflammatory cytokines and decreased the expression of inducible nitric oxide synthase, cyclooxygenase-2 in LPS-stimulated BV2 microglial cells. Furthermore, it inhibited the phosphorylation and degradation of inhibitory κBα and decreased the nuclear translocation and phosphorylation of nuclear factor-κB (NF-κB). Moreover, QAE inhibited the phosphorylation of extracellular signal-regulated kinase, p38 and c-Jun N-terminal kinase, which is known as mitogen-activated protein kinase (MAPK). Additionally, QAE treatment increased heme oxygenase-1 (HO-1) expression by activating the nuclear factor erythroid 2-related factor 2 (Nrf2) signaling, thereby ameliorating LPS-induced intracellular hydrogen peroxide production. Finally, it was found that catechin and taxifolin, two phytochemicals of QAE, also reduced the expression of inflammatory mediators. These findings suggest that QA is beneficial for preventing microglia-mediated neuroinflammatory response through the inhibition of NF-κB, MAPK and the activation of Nrf2/HO-1 signaling pathways.